A challenging case of transvenous lead extraction - Tolga Aksu; Tumer Erdem Guler; Kazim Serhan Ozcan; Ismail Erden (KARE Publishing, 2015)
A 72-year-old male patient with a 7-year history of cardioverter-defibrillator (ICD) implantation was admitted to our clinic with pocket infection. One year prior to this admission, he had undergone an unsuccessful extraction procedure at another clinic, during which the older broken ICD lead had been left in place and a newer ICD lead implanted via the same pocket. The newer and older leads were extracted by mechanical dilator sheath and needle eye snare respectively.